An introductory CFD analysis study of novel cavity vane driven wind turbine blade design - Ashwindran, S. N.; Azizuddin, Abd Aziz; Oumer, A. N.; Azli, Abd Razak (Faculty of Mechanical Engineering, Universiti Teknologi MARA (UiTM), Malaysia., 2020)
Climate in Malaysia is heavily influenced by monsoon seasons, where the wind speed pattern is inconsistent and highly unsteady. Existing commercial wind turbines are only designed to accommodate high wind speed regions. In order to harvest energy in Malaysia, design modification is required on conventional wind turbine blade. This paper presents an introductory computational investigation of proposed drag driven vertical axis wind turbine. The objective of this research is to investigate the factors that govern the aerodynamics attributes of the proposed design. The design is simulated in 2D using sliding mesh technique via FLUENT based on URANS model. Previous mesh dependency study shows that fine and medium grid topology indicated a good agreement. In this numerical study, the proposed wind turbine is simulated based on SST k-ω turbulent transport model under fine grid spatial discretization. The design is analyzed under the influence of constant freestream velocity of 25 m/s in order to study the behavior of the turbine at high speed and low RPM. Result shows that high static pressure of 64.8 kPa exerts on the returning blade 1 which overwhelms the motion of advancing blade. Blade 1-3 indicated stable numerical values after 216°. Hence, the governing factors in terms of flow properties that affected the wind turbine are studied for future improvement. It is found that the cavity vane of the proposed design requires modification in order to improve moment.